USING INFRARED THERMOGRAPHY FOR DETAILED MONITORING OF CABBAGE WATER AND HEAT STRESS - Tarek FOUDA; Eltaher MADY; Nouri AL BAY; Ashraf SWIDAN; Shaimaa SALAH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The research was conducted on the farm of the agricultural research station, Agricultural Research Center, Tripoli, Libya (latitude of 32° 12' 25'' and longitude of 13° 62' 16'') during the season of 2021-2022. Cabbage and lettuce crops were planted at greenhouse condition in November 2021. The objective of this study was using alternate representations of infrared thermography IR to detect the vegetative indicators addition to continuously monitor cabbage and lettuce plants growing conditions for discrimination plants stresses under the shortage of nitrogen and irrigation water, using four levels of nitrogen fertilization (0, 50, 100 and 150% of Nitrogen recommended). Also four levels of water regime (50%, 75%, 100% and 125% of ETc) . The leaf-to-air temperature difference (ΔT), The relationship between the temperature of the canopy (Tc) and temperature of soil (Ts), pair is best suited to ﬁnd the plant under water stress. Water stress index (CWSI) and stomatal conductance index (Ig) using various reference and non-reference thresholding techniques were tested. In this research a thermal imaging system was used to measure the leaf-temperature changes of several crops according to plant stresses. Results showed by applying 100% fertilization and 100% ETc to cabbage. The heat stress was the highest as MTD, maximum temperature difference, normalized relative canopy temperature were 8 and 0.32 C when the water stress as CWSI, IG index of stomatal conductance were 0.5 and 4.15 for cabbage in100% ETC and 150%F. Finally, possibility of using infrared thermography for detailed and continuous monitoring showed its ability to distinguish and show the thermal and water stress of plants under nitrogen and water deficiency.